EXAMINATIONS OF THE AMERICAN INSTITUTE OF ACCOUNTANTS. - Kohler, Eric L. (The Accounting Review, 1927)
Abstract Among the provisions of the constitution of the American Institute of Accountants, it is stated that one of the objects of the Institute is "to develop and improve accountancy education." The endowment fund was established largely for the promotion of this object; and for years the Committee on Education has been functioning with great vigor in an attempt to analyze and formulate the trend of accounting instruction. In previous regional meetings and in sessions of the Institute, educators have been called upon freely to express their ideas as to the problem which they have. Each year the recommendations which have proceeded from discussions have become more and more specific. Yet is appears that nothing has been said as to the importance to the academic field of the semi-annual examinations set by the Institute's Board of Examiners. Members of the teaching profession have regarded these examinations, especially since their adoption by thirty or more state boards of examiners, as furnishing important criteria for student instruction. No doubt the Institute's Board of Examiners, with appropriate professional modesty, would disclaim any effort, direct or indirect, to invade or in any way to influence the profession of teaching. But a denial of intent cannot alter the use to which the examinations have been put.